2019
DOI: 10.24200/sci.2019.5637.1391
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Comparison of Flow and scour Patterns around a Single and Triple Bridge Piers Located at a sharp 180 degrees Bend

Abstract: Placement of bridge piers along rivers creates a complex 3D flow pattern which disrupts normal river flow and the resulted turbulence erodes alluvial sediments around the pier. In this research, SSIIM model has been used to simulate flow and scour patterns when no pier, one pier, and triple piers are placed at a 180 degrees bend and the results are compared with those of experiments. The piers are vertical. The simulated channel was 1 m wide with a U-turn having the relative curvature radius of 2 carrying a vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Asadollahi et al [26] compared experimental and numerical data under different conditions either with or without the presence of piers to examine the validation of SSIIM numerical model under such conditions, and they proved the capability of this model in simulating the flow and sediments in the sharp bend. In the following, 3D flow velocities have been compared with the aim of presenting an instance of the results obtained from the comparison between numerical and experimental data in the case of no piers installed.…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Asadollahi et al [26] compared experimental and numerical data under different conditions either with or without the presence of piers to examine the validation of SSIIM numerical model under such conditions, and they proved the capability of this model in simulating the flow and sediments in the sharp bend. In the following, 3D flow velocities have been compared with the aim of presenting an instance of the results obtained from the comparison between numerical and experimental data in the case of no piers installed.…”
Section: Validationmentioning
confidence: 99%
“…Results of their work suggested that with the piers installed in perpendicular and streamwise directions at the 60-degree angle, the maximum area of the scour hole occurred around the piers and sediment piles were created at the downstream side of the piers. Asadollahi et al [26] made a numerical and experimental comparison of the flow and scour patterns around single and triad piers installed in a 180-degree sharp bend. Results obtained from such comparisons are indicative of an appropriate correspondence of numerical data and the capacity of SSIIM [27][28][29][30] in simulation of flow and scour patterns with the maximum error of scour and sedimentation reported for 4%.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the shapes of topography were similar for a different spacing and scour duration. Asadollahi et al (2019) and Asadollahi et al (2020) compared the numerical and experimental results on the flow and scour patterns around single and triad piers placed at a 180-degree bend channel. The comparison referred to the appropriate correspondence of the numerical data and the great capacity of SSIIM in modeling the flow and sediment transport with merely 4% of the maximum error recorded for the scour and sedimentation.…”
Section: Article History Abstractmentioning
confidence: 99%
“…The most incredible scour depth was 3.3 times the pier diameter at an intensity of 8.5 and followed a logarithmic curve. Although local scour at a bend is extremely important, and numerous studies have been undertaken to date, most of the research within the curve was based on the incipient motion at threshold intensity, some of which were as follows: [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%